The Effect of Bio-Fertilizer Concentration and NPK Fertilizer Dosage on the Growth and Yield of Melon (Cucumis melo L.) Merlin Variety - Alfani Ahsanul Ilmi; Juli Santoso; Sutini Sutini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Melon (Cucumis melo L.) is a fruit known for its sweet and refreshing taste. Traditionally, melon cultivation has relied on conventional farming methods. The use of biofertilizers offers an alternative to reduce dependency on synthetic fertilizers. This study aimed to enhance the production of healthy, high-yielding melon plants by substituting Mutiara NPK fertilizer with Bioto Grow Gold (BGG) biofertilizer. Conducted in Sukosongo Village, Kembangbau District, Lamongan Regency, East Java, the experiment employed a factorial Completely Randomized Design (CRD).Two factors were tested: BGG fertilizer at four concentrations (0 ml/L [P0], 1 ml/L [P1], 2 ml/L [P2], and 4 ml/L [P3]) and NPK fertilizer at four doses (0 g/plant [N0], 60 g/plant [N1], 70 g/plant [N2], and 80 g/plant [N3]). Results indicated that BGG fertilizer influenced both vegetative and generative growth variables, as did the Mutiara NPK fertilizer doses. The optimal combination was achieved with a BGG concentration of 3 ml/L and an NPK dose of 70 g/plant, which significantly increased the sucrose content in melons. Keywords: Bioto Grow Gold fertilizer, Biofertilizer, Melon, NPK Mutiara fertilizer.